"Fostering employee engagement through employee perceptions about diversity and inclusion in an international firm" - Hossain, Sylvia; Hossain, Sylvia (My University, 2025)
With the rapid proliferation of a diverse workforce in international businesses, workplace challenges have substantially increased, and firms are striving to find strategies that effectively motivate employees to bring fresh ideas to the table to redouble firm-level innovation and productivity. Diversity and Inclusion (D&I is an undeniably important strategy that meets individual needs to enhance job satisfaction and help the firm reach its maximum potential. The primary goal of this study is to investigate whether firm-level diversity and inclusion initiatives affect employee engagement, i.e., willingness to contribute to the organization,” and answer the research question, “How do employees perceive the influence of D&I initiatives on employee engagement?” The theoretical framework covers relevant literature, focusing on Diversity and Inclusion, employee engagement, and other aspects that induce employee engagement within the organization. The semi-structured interviews were conducted within the frames of multiple case studies to examine the above-mentioned research question in diverse businesses This study finds that considering D&I as one of the firm’s core values and integrating it within organizations’ core strategies motivates employees to remain engaged. This thesis highlights the connection between two factors of multinational corporations (MNCs) operating with diverse workforces and how D&I accelerates inclusive workplaces to promote employee engagement. Furthermore, this study finds the importance of diversity and inclusion management in fostering employee engagement through increased job satisfaction.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business